Impact of ultrasound-assisted extraction on physical properties, antioxidant activity, and colorimetric pH-response of blackcurrant pomace extract - Zainal Arifin, Maryam Adilah; Zainal Abedin, Nur Hanani; Mohamad Azman, Ezzat; Ab Razak, Nor Asma; Mohd Adzahan, Noranizan (American Chemical Society, 2024)
This study aimed to evaluate the efficiency of ultrasound in extracting phenolic compounds from dried blackcurrant pomace (DBP) compared to the traditional extraction method. DBP extraction was carried out using maceration (control) and three levels of ultrasound power (256, 448, and 640 W) for 5, 15, and 25 min. Ultrasound-assisted extraction (UAE) of DPB resulted in a 40% higher yield than macerated samples (9.35%). Specifically, UAE Sample C (256 W, 25 min) significantly improved the total monomeric anthocyanin content (by 33%), total phenolic content (up to 16%), and radical scavenging activity (by 26%) compared to the control. The morphology of the ultrasound-treated DBP showed porous cells that resembled a hollow honeycomb structure. The phenolic profiling of ultrasound-treated DBP showed significantly higher contents of anthocyanin, hydroxycinnamic acid, and flavonols than the control. Ultrasound can also extract compounds such as myricetin and quercetin, which typically require strong acids and high temperatures, thus proving that ultrasound is a better extraction method than conventional extraction.